Ochotnikova O.V. Theoretical approaches to definition of the concept “meritocracy” as the mechanism of formation of the administrative elite - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
The article analyzed contemporary approaches to the concept of “meritocracy”, analyzes the notion of “meritocracy as a mechanism for the formation of a management elite”, the principles of meritocracy as a mechanism for the formation of a governing elite should be considered: objectivity, purposefulness, constancy, legitimacy, performance, measurability